Diagnosis in PANDAS: An Update - Cabrera-Mendoza, Brenda; Genis-Mendoza, Alma D.; Nicolini, Humberto (Current Psychiatry Research and Reviews, 2019)
Background: The last twenty years have seen major advancements in unraveling the etiology and the identification of biological markers of Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococci (PANDAS). However, this body of evidence has not yet been translated into a clinical setting. Objective: We will review the most important studies to date on PANDAS, emphasizing those whose advances could improve the diagnosis of these disorders. We also suggest the need for updated diagnosis criteria integrating the recent findings from the hereby included studies. Methods: Consulting the PubMed database, a literature review of the last twenty-one years (between 1998 and 2019) was carried out using the terms “PANDAS” and “pediatric autoimmune neuropsychiatric disorders” in combination with “diagnosis” and “markers”. The search resulted in 175 hits from which we selected clinical cases, original investigations, and clinical reviews. Results: This review offers a compilation of the most important studies performed to date regarding the clinical presentation and potential biological markers of PANDAS. Moreover, we suggest the refinement of some aspects in the current diagnosis criteria, such as focusing on specific symptoms and the inclusion of neuroimaging and peripheral markers. Conclusion: The identification of specific biological markers in PANDAS is crucial for its diagnosis and opportune treatment. Future research will determine whether PANDAS require separated diagnostic and therapeutic measures or if it should be included in recently proposed categories such as Pediatric Acute Neuropsychiatric Syndrome (PANS) or Childhood Acute Neuropsychiatric Syndrome (CANS).
Keywords: diagnosis